Development and standardization of an attitudinal assessment scale for virtual laboratory integration in science education - Kaliappan, Thiyagu; Thomas, Mary Vineetha; Thangan, Santhosh; Padmanaban, Srinivasan (Institute of Advanced Engineering and Science, 2025)
The escalating adoption of virtual laboratories (V-Labs) within science education highlights an urgent need for an established metric to evaluate student attitudes toward their implementation. This research introduces a detailed attitudinal assessment scale, specifically designed to measure various aspects of student perceptions such as perceived effectiveness, satisfaction, pedagogical impact, usability, and overall influence on educational outcomes. The development process involved an elaborate procedure for generating items based on a thorough review of existing literature and insights from subject matter experts, followed by a pilot test conducted on a select cohort of science students aimed at refining the items. Employing stringent empirical methods including detailed item analysis and factor analysis, the research confirmed the scale's high reliability, evidenced by a Cronbach’s alpha of .983. Factor analysis identified five principal components that collectively encompass technological, psychological, and educational factors shaping student attitudes toward virtual labs. This scale is crucial for educators and administrators for effectively assessing and enhancing virtual lab integrations. It provides valuable insights that can inform the enhancement of virtual lab configurations, curriculum integration, and teaching strategies, ultimately improving student engagement and learning outcomes. The creation of this scale addresses a critical void in academic research by offering a standardized method to assess student attitudes and also paves the way for future investigations into the extensive implications of virtual labs in diverse educational settings and disciplines.